Values Of Islamic Education In The “Suran” Tradition Of The Salamerta Village Community, Kab. Banjarnegara - Mawi Khusni Albar; Eva Lustika Sari (At-Tarbiyat, 2021)
This article elaborates the theory of the suran tradition in Salamerta Village, Mandiraja District, Banjarnegara Regency and tries to explore the values ​​of Islamic education inherent in it. The research uses descriptive-qualitative methods, and is included in field research or field research. In obtaining the data, the instruments that the researcher uses are in-depth interviews, observations, and studies of related documents. The analysis used by the researcher is as stated by Mohd. Soehadha, namely by reducing data, displaying data, and drawing conclusions. In clarifying the validity of the data, the researcher extended the participation, and triangulated the sources and methods. From the research conducted, it can be seen that the values ​​of Islamic education contained in the Suran tradition include: discipline, strengthening ties of friendship, endeavor, love for the Prophet Muhammad, the teachings of giving alms and gratitude.